The Jinn-Bot of Shantiport - Basu, Samit (Tordotcom, Tor Publishing Group, 2023)
"Shantiport was supposed to be a gateway to the stars. But the city is sinking, and its colonist rulers aren't helping anyone but themselves. Lina, a daughter of failed revolutionaries, has no desire to escape Shantiport. She loves her city and would do anything to save its people. This is, in fact, the plan for her life, made before she was even born. Her brother, Bador, is a small monkey bot with a big attitude and bigger ambitions. He wants a chance to leave this dead-end planet and explore the universe on his own terms. But that would mean abandoning the family he loves--even if they do take him for granted. When Shantiport's resident tech billionaire coerces Lina into retrieving a powerful artifact rumored to be able to reshape reality, forces from before their time begin coalescing around the siblings. And when you throw in a piece of sentient, off-world tech with the ability to grant three wishes into the mix... None of the city's powers will know what hit them"--